A study of a group of genes involved in the hair growth cycle. (2nd May 2020) - Hawkshaw, N.J.; Hardman, J.A.; Alam, M.; Jimenez, F.; Paus, R.
Summary: Individual hairs grow from follicles which go through a cycle of different stages. During 'anagen' the hair is actively growing, in 'catagen' the follicle shrinks, while 'telogen' is the resting phase when the hair sheds before the next anagen. Abnormal hair growth usually reflects an abnormal hair cycle. For example, failure to re‐enter anagen from telogen, or short duration of anagen, cause poor hair growth, while excessive switching from telogen back to anagen causes excessive hair. If we could understand what controls these stages, it might be possible to develop effective treatments. Previously, scientists have managed to grow individual human anagen hair follicles in the laboratory but could only study the switch from anagen to catagen. The authors of this latest study, from the UK, Spain, Germany and the USA, managed for the first time to isolate human telogen and early anagen hairs. They used scalp samples from five men undergoing hair transplantation and dissected out the relevant hairs under the microscope. Using specific antibodies (a type of protein in the body) to examine telogen follicles they discovered that a group of genes called the WNT pathway induce anagen by prompting certain cells in the hair germ (part of the follicle) to multiply. By studying a whole range of proteins that switch WNT processes on or off they were able to build up a picture of events occurring at the start of anagen which will help future scientists to develop targeted treatments for hair disorders. This is a summary of the study: Deciphering the molecular morphology of the human hair cycle: Wnt signalling during the telogen–anagen transformation. Abstract : Linked Article: Hawkshaw et al. Br J Dermatol 2020; 182 :1184–1193